Representation of Gender Roles in the ELT Textbook for Elementary School Students - Jauharoh Nabila (Faculty of Teacher Training and Education, 2026)
English language teaching (ELT) textbooks serve not only as a resource for language learning but also as a medium that can shape students’ understanding of social values, including gender roles. This study aims to describe the representation of gender roles in the ELT textbook for elementary school students titled My Next Words for Grade 4, published by the Ministry of Education and Culture of the Republic of Indonesia. This study employed a Qualitative Content Analysis (QCA) method adapted from Schreier (2012). Data were collected from the textual and visual content in the textbook and then analyzed using Moser’s (2012) framework of gender roles, which includes productive, reproductive, and community roles. The results revealed 15 instances representing gender roles. Of the three categories of gender roles according to Moser, only productive and reproductive roles were found, while community roles did not appear in the textbook material. Reproductive roles were the most dominant category with nine data points, represented through domestic and caregiving activities such as cleaning the house, cooking, watering plants, waking children up, and going at the market, with female characters depicted more frequently than male characters. Meanwhile, productive roles were found in six instances depicting work activities, such as police officers, farmers, teachers, and salespeople, with male characters being represented more frequently than female characters. These findings indicate that the representation of gender roles in textbooks still tends to perpetuate traditional gender role divisions, in which women are more often associated with domestic responsibilities, while men are more frequently associated with productive work. Therefore, textbook authors and teachers are advised to present a more balanced representation of gender and to encourage critical discussions about gender equality in the learning process. Further research is recommended to analyze more textbooks from various educational levels, publishers, and curricula in order to obtain a more comprehensive picture of gender role representation in ELT textbooks in Indonesia.
:: Finalisasi file repositori 23 Juli 2026_Kurnadi
Keywords: Representation; ELT Textbook; Elementary School Students